(3fXQjI GdJhRjY (B/s - (3CHh fGUQ, YJGH CMeOs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj ddfTQ(B;(3CLfGOjf ddfTQ hGdJhRjY(B, s, 2007)
(3GdJYQja HfXQjI GdJhRjY, JMOjO CKeGf NOeGJ YfGUQ GdEfJGL hMcegG aj Gdabg GdESdGejs
(3HHdjhZQGajG(B: (3U(B. 135s
Keywords: (3EOGQI GdEfJGLs; (3GdEbJUGO GdESdGejs